IMPLEMENTASI REPOSITIONING L-MEN DALAM KEGIATAN KOMUNIKASI PEMASARAN - Hafiar, Hanny; Sani, Anwar; Nur Ihsan, Mega Farras i (Communication, 2016)
AbstractThis research purpose is to know the communications strategy of L-Men, the product attributes of L-Men, and the positioning statement of the L-Men product in their repositioning strategy. The method used in this research is descriptive with qualitative data. The subject of this research is individuals involved in the implementation of L-men's repositioning, from the process of planning to implementation. The Data is obtained through passive participant observation, semi-structured interview, and literature. The result of this research shows that L-Men repositioning communication strategy with management L-Men consisted of brand marketing, digital, public relations, customer relations, promotions, and involvements of Perbasi and non-gym athletes as communicator, to bring out the message that L-Men is a product for those who desire ideal and athletic body shape, through media and face to face interaction with audience through events and programs, with target audiences ranging from 17 years old until 35 years old male who partake in healthy lifestyle and the needs of nutrients for the formation of muscle mass and improving sports performance, with the end goals of increasing the product awareness and also the number of sales. The attributes that L-men possessed in its repositioning strategy are packaging design, advertising concept, content marketing, and event. The repositioning as stated by the positioning statement is “Effective Nutrients for Male Ideal and Athletic Body Shape”.Keywords: implementation, repositioning, attributeAbstrakTulisan ini bertujuan untuk mengetahui bagaimana strategi komunikasi yang dilakukan L-Men, bagaimana atribut-atribut produk yang disampaikan L-Men, serta untuk mengetahui bagaimana positioning statement baru yang dimiliki L-Men dalam menerapkan repositioning.Metode penelitian yang digunakan adalah deskriptif dengan jenis data kualitatif. Subjek dalam penelitian mengenai hasil repositioning L-Men ini merupakan individu yang terlibat dalam pelaksanaan repositioning, dari masa perencanaan hingga pelaksanaan. Pengumpulan data diperoleh melalui observasi partisipasi pasif, wawancara semi terstruktur, dan studi pustaka.Hasil penelitian menjelaskan bahwa: Repositioning L-Men merupakan strategi komunikasi yang dilakukan oleh manajemen L-Men sebagai komunikator yang terdiri dari brand marketing, digital, public relations, customer relations, promotions (SPG), serta melibatkan pihak eksternal seperti Perbasi dan atlet-atlet non-gym, dengan pesan yang ingin disampaikan adalah L-Men merupakan produk untuk membentuk tubuh yang ideal dan atletis, melalui media serta berhadapan langsung dengan audiens melalui event dan program, dengan target sasaran pria berusia 17 sampai 35 tahun yang menyukai gaya hidup sehat dan membutuhkan nutrisi untuk pembentukan massa otot dan meningkatkan performa olahraga, dengan efek yang diharapkan adalah meningkatkan awareness produk dan meningkatkan jumlah penjualan. Atribut-atribut yang dimiliki L-Men dalam repositioning adalah desain packaging, konsep iklan, konten marketing, dan event. Repositioning ini dinyatakan dalam positioning statement, yaitu “Nutrisi Efektif untuk Pria Membentuk Tubuh Ideal dan Atletis”.Kata kunci: implementasi, repositioning, atribut